Prevalence of Opioid Dependence and Opioid Agonist Treatment in the Berlin Custodial Setting: A Cross-Sectional Study - von Bernuth, Kira; Seidel, Peter; Krebs, Julia; Lehmann, Marc; Neumann, Britta; Konrad, Norbert; Opitz-Welke, Annette (Frontiers in Psychiatry, 2020)
Background: Among people living in detention, substance use is highly prevalent, including opioid dependence. Opioid agonist treatment (OAT) has been established as an evidence-based, first-line treatment for opioid dependence. Despite high prevalence of opioid dependence, conclusive data regarding its prevalence and the OAT practice in German prisons is scarce; rather, the existing data widely diverges concerning the rates of people in detention receiving OAT. Methods: We conducted a cross-sectional survey of all detention facilities in Berlin. On the date of data collection, a full census of the routine records was completed based on the medical documentation system. For each opioid dependent individual, we extracted sociodemographic data (i.e., age, sex, and non-/German nationality, whether people experienced language-related communication barriers), information about OAT, comorbidities (HIV, hepatitis C, schizophrenia), and the detention center, as well as the anticipated imprisonment duration and sentence type. The data was first analyzed descriptively and secondly in an evaluative-analytical manner by analyzing factors that influence the access to OAT of people living in detention. Results: Among the 4,038 people in detention in the Berlin custodial setting under investigation, we identified a 16% prevalence of opioid dependence. Of the opioid-dependent individuals, 42% received OAT; 31% were treated with methadone, 55% were treated with levomethadone, and 14% were treated with buprenorphine. Access to OAT seemed mainly dependent upon initial receipt of OAT at the time of imprisonment, detention duration, the prisons in which individuals were detained, German nationality, and sex. The overall prevalence of HIV was 4–8%, hepatitis C was 31–42%, and schizophrenia was 5%. Conclusions: The prevalence of opioid dependence and access to OAT remains a major health issue in the custodial setting. OAT implementation must be especially intensified among male, non-German, opioid-dependent individuals with a short detention period. Treatment itself must be diversified regarding the substances used for OAT, and institutional treatment differences suggest the need for a consistent treatment approach and the standardized implementation of treatment guidelines within local prison’s standard operating procedures. Testing for infectious diseases should be intensified among opioid-dependent people living in detention to address scarcely known infection statuses and high infection rates.